Visible light photocatalytic degradation of sulfanilamide enhanced by Mo doping of BiOBr nanoflowers - Wu, Yunyun; Ji, Haodong; Liu, Qiming; Zhaoyang Sun; Peisheng Li; Ding, Peiren; Guo, Ming; Xiaohong Yi; Wenlu Xu; Chong-Chen Wang; Gao, Shuai; Qiang Wang; et al. (Journal of Hazardous Materials, 2022)
Design of high-efficiency visible light photocatalysts is critical in the degradation of antibiotic pollutants in water, a key step towards environmental remediation. In the present study, Mo-doped BiOBr nanocomposites are prepared hydrothermally at different feed ratios, and display remarkable visible light photocatalytic activity towards the degradation of sulfanilamide, a common antibacterial drug. Among the series, the sample with 2% Mo dopants exhibits the best photocatalytic activity, with a performance 2.3 times better that of undoped BiOBr. This is attributed to Mo doping that narrows the band gap of BiOBr and enhances absorption in the visible region. Additional contributions arise from the unique materials morphology, where the highly exposed (102) crystal planes enrich the photocatalytic active sites, and facilitate the adsorption of sulfanilamide molecules and their eventual attack by free radicals. The reaction mechanism and pathways are then unraveled based on theoretical calculations of the Fukui index and liquid chromatography/mass spectrometry measurements of the reaction intermediates and products. Results from this study indicate that deliberate structural engineering based on heteroatom doping and morphological control may serve as an effective strategy in the design of highly active photocatalysts towards antibiotic degradation.
Keywords: Band gap; Degradation; Mo-doped BiOBr; Photocatalytic; Sulfanilamide; Visible light